Alexithymia and its relationship to personality traits Field study on a sample of elderly people in Damascus Governorate (Journal of Hama University, 2026)
The aim of present study was to examine the relationship between Alexithymia and personality traits among a sample of the elderly living in Damascus Governorate، and to investigate the differences in those variables،  and to  identify the impact of the interaction between the impact and the size of the study variables Alexithymia. A self Toronto Alexithymia Scale (TAS 20). and Personality traits scale were administered to a sample composed of (60) elderly (30 males، and 30 females) .The average age of the sample group was (70) years، (SD= 3.49)، Age ranged between (65-75) years.The results of the study showed tgat the most common feature of the elderly, the members the reserach, is the cgaracteristic of the Extraversion. The results of the study also showed a negative correlation between alexithymia and personality traits in the elderly, except for the neuroticism dimension, which had a positive correlation with alexithymia.. As well as the presence of significant differences among the elderly males and females Alexithymia in favor of females. The results also showed that there is a close interaction between sex، and Alexithymia. A set of proposals jas been presented to the results of the current study, which may help the elderly reduce the level Alexithymia, and increasing their ability to recognize and express feelings
Keywords: personality traits; Elderly